2006
DOI: 10.1017/s106828050000678x
|View full text |Cite
|
Sign up to set email alerts
|

The Welfare Effects of Pfiesteria-Related Fish Kills: A Contingent Behavior Analysis of Seafood Consumers

Abstract: We use contingent behavior analysis to study the effects of pfiesteria-related fish kills on the demand for seafood in the Mid-Atlantic region. We estimate a set of demand difference models based on individual responses to questions about seafood consumption in the presence of fish kills and with different amounts of information provided about health risks. We use a random-effects Tobit model to control for correlation across each observation and to account for censoring. We find that (i) pfiesteria-related fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 18 publications
(16 reference statements)
1
9
0
Order By: Relevance
“…Our results differ from previous studies in other ways. For example, Wessells, Kline, and Anderson (1996) and Parsons, Morgan, Whitehead, and Haab (2006) found that seafood consumption decreased with negative information and increased with some types of positive information. Smith et al (1988); Hu, Adamowicz, and Veeman (2009);Haab et al (2010) found that negative food safety information tends to decrease consumption, while positive information does not necessarily have the opposite effect.…”
Section: Resultsmentioning
confidence: 99%
“…Our results differ from previous studies in other ways. For example, Wessells, Kline, and Anderson (1996) and Parsons, Morgan, Whitehead, and Haab (2006) found that seafood consumption decreased with negative information and increased with some types of positive information. Smith et al (1988); Hu, Adamowicz, and Veeman (2009);Haab et al (2010) found that negative food safety information tends to decrease consumption, while positive information does not necessarily have the opposite effect.…”
Section: Resultsmentioning
confidence: 99%
“…The food safety literature includes a large number of studies related to pesticide risk (Florax, Travisi, & Nijkamp, 2005). There are relatively fewer studies that examine seafood safety (e.g, Huang, Haab, & Whitehead, 2004; Parsons, Morgan, Whitehead, & Haab, 2006; Wessells, Kline, & Anderson, 1996). There are fewer still that focus on oyster consumption.…”
Section: Literaturementioning
confidence: 99%
“…Investigators reported human illness following occupational exposure to laboratory cultures of the organism, and fish collected from areas of P. piscicida blooms exhibited superficial ulcers [ 36 , 37 ]. Notably, even without evidence that local seafood was contaminated with either P. piscicida or any associated toxin, consumers chose not to eat seafood caught from the Chesapeake Bay, or served in restaurants along the shoreline [ 38 ]. There is conflicting evidence regarding whether Pfiesteria piscicida kills fish by a combination of toxic and physical means or whether the fish kills were due to anoxia or hypoxia with superficial ulcers attributed to Aphanomyces invadans infections [ 39 , 40 , 41 , 42 ].…”
Section: Example Animal Sentinel Systems and Eventsmentioning
confidence: 99%